2021
DOI: 10.1159/000516671
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Diabetes Mellitus to Efficacy of Immune Checkpoint Inhibitors in Patients with Advanced Non-Small Cell Lung Cancer

Abstract: <b><i>Introduction:</i></b> Immune checkpoint inhibitors (ICI) are the new standard therapy in patients with metastatic NSCLC (mNSCLC). Metformin, previously associated with improved chemotherapy efficacy in diabetic and nondiabetic cancer patients, was recently associated with increased ICI efficacy. In this study, we aimed to explore the correlations between diabetes mellitus (DM), metformin use, and benefit from ICI in mNSCLC patients. <b><i>Methods:</i></b> A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…There is growing evidence that metformin exerts its anticancer effects by inhibiting tumor metabolism and that metformin may be a potential candidate for combination therapy in NSCLC. A number of preclinical studies have reported good results of metformin acting concurrently with radiotherapy, tyrosine kinase inhibitors (TKIs) and ICIs in NSCLC ( 104 107 ), which has encouraged the use of combination therapies. In a meta-analysis of 14 clinical studies comprising 3,856 patients, the combination of metformin with standard antineoplastic drugs significantly improved OS in patients with lung cancer ( 108 ).…”
Section: Clinical Progress Of Metformin Combined With Standard Anticancer Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing evidence that metformin exerts its anticancer effects by inhibiting tumor metabolism and that metformin may be a potential candidate for combination therapy in NSCLC. A number of preclinical studies have reported good results of metformin acting concurrently with radiotherapy, tyrosine kinase inhibitors (TKIs) and ICIs in NSCLC ( 104 107 ), which has encouraged the use of combination therapies. In a meta-analysis of 14 clinical studies comprising 3,856 patients, the combination of metformin with standard antineoplastic drugs significantly improved OS in patients with lung cancer ( 108 ).…”
Section: Clinical Progress Of Metformin Combined With Standard Anticancer Drugsmentioning
confidence: 99%
“…Promising results have also been reported by two recent studies of metformin in combination with TKIs and ICIs, respectively, which suggested that metformin was able to significantly improve PFS and OS in patients with NSCLC by overcoming acquired resistance to TKIs and enhancing PD-1 blockade by anti-PD-1 antibodies, respectively ( 101 , 102 ). Other studies ( 111 114 ) suggested that metformin may increase tumor response to ICI through a variety of mechanisms, including upregulation of CD8 + tumor-infiltrating lymphocytes and their function, downregulation of myeloid suppressor cells with immunosuppressive effects, reduction of tumor hypoxia, anti-angiogenic effects and shifting the composition of the patient's gut flora to bacterial strains that may respond better to immunotherapy ( 107 ). Although it has been suggested that metformin treatment may exert a synergistic antitumor effect with ICIs, the study by Jacobi et al ( 107 ) did not obtain any positive association between metformin and ICIs in the treatment of patients with diabetes combined with NSCLC.…”
Section: Clinical Progress Of Metformin Combined With Standard Anticancer Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of immunotherapy to cancer patients with obesity are ambiguous [ 108 ]. Diabetes has negative effects on ICB in metastatic NSCLC [ 109 ]. Mechanistic studies are needed to shed light on the linkage between metabolic pathologies and immunotherapy efficacy.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…However, since immunotherapy has been implemented widely in clinical practice, the effect of DM among patients treated with ICIs should be clarified. Additionally, the peripheral blood glycated hemoglobin A1c (HbA1c) was a regular indicator for DM diagnosis and treatment evaluation, previous studies have reported the negative prognostic role of higher HbA1c levels in patients who underwent surgical resection, while the reported results are too scarce for a robust conclusion to be drawn in these patients received ICIs at present, although pembrolizumab therapy has achieved obvious clinical benefits (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%